Exercise Stress Testing in Children with Metabolic or Neuromuscular Disorders - Tim Takken; Wim G. Groen; Erik H. Hulzebos; Cornelia G. Ernsting; Peter M. van Hasselt; Berthil H. Prinsen; Paul J. Helders; Gepke Visser (International Journal of Pediatrics)
The role of exercise as a diagnostic or therapeutic tool in patients with a metabolic disease (MD) or neuromuscular disorder (NMD) is relatively underresearched. In this paper we describe the metabolic profiles during exercise in 13 children (9 boys, 4 girls, age 5–15 yrs) with a diagnosed MD or NMD. Graded cardiopulmonary exercise tests and/or a 90-min prolonged submaximal exercise test were performed. During exercise, respiratory gas-exchange and heart rate were monitored; blood and urine samples were collected for biochemical analysis at set time points. Several characteristics in our patient group were observed, which reflected the differences in pathophysiology of the various disorders. Metabolic profiles during exercises CPET and PXT seem helpful in the evaluation of patients with a MD or NMD.